The Effect of Angipars on Diabetic Neuropathy in STZ-Induced Diabetic Male Rats: A Study on Behavioral, Electrophysiological, Sciatic Histological and Ultrastructural Indices - Nasser Zangiabadi; Hossein Mohtashami; Mahboobeh Hojatipour; Mandana Jafari; Majid Asadi-Shekaari; Mohammad Shabani (The Scientific World Journal)
Diabetes mellitus is the most common metabolic disease with a high prevalence rate in human society that eventually leads to the peripheral nervous system complications in a great number of patients. In the present study, the effects of Angipars on nerve conduction velocity, histological alterations, and behavioral indices were investigated. Diabetes was induced in male rats by intraperitoneal injection of streptozotocin (STZ). Six weeks after STZ injection, animals were divided into five groups control, vehicle, and 3 experimental groups. The vehicle group received 1 mL distilled water daily for two weeks and three experimental groups received, respectively, intraperitoneal injection of 5, 10, and 20 mg/kg Angipars daily for two weeks. Intraperitoneal injection of Angipars, in some extent, could significantly improve behavioral indices of the experimental groups as compared to the vehicle group. Furthermore, mean nerve conduction velocity in the vehicle group showed significant difference with that in the control and the 2nd experimental groups; therefore, Angipars could increase nerve conduction velocity in neuropathic rats. Overall, Angipars exerted positive effects on the treatment and reduction of physiologic symptoms and improvement of sciatic morphological injuries in neuropathic rats.